Comparisons of the clinical outcomes of thoracoscopic sympathetic surgery for palmar hyperhidrosis: R4 sympathicotomy versus R4 sympathetic clipping versus R3 sympathetic clipping - Joo, Seok; Lee, Geun Dong; Haam, Seokjin; Lee, Sungsoo (Journal of Thoracic Disease; Vol 8, No 5 (May 01, 2016): Journal of Thoracic Disease, 2016)
Background: Thoracoscopic sympathetic surgery is regarded as a definitive treatment for palmar hyperhidrosis. However, the optimal surgical strategy remains unclear. The aim of this study was to compare outcomes based on the level and type of sympathetic disconnection in patients with palmar hyperhidrosis. Methods: From January 2009 to December 2014, 101 patients with palmar hyperhidrosis underwent thoracoscopic sympathetic surgery at Gangnam Severance Hospital. Complete follow-up information was obtained from 59 patients. We retrospectively analyzed the results of operation, degree of palmar sweating (%), grade of compensatory sweating (none, mild, moderate, severe, very severe), grade of satisfaction (very satisfied, satisfied, moderate, dissatisfied, very dissatisfied), and recurrence/failure. Results: R4 sympathicotomy, R4 sympathetic clipping, and R3 sympathetic clipping were performed in 16, 20, and 23 patients, respectively. The mean degree of palmar sweating after sympathetic surgery was not significantly different between these three groups (17.50% vs. 27.00% vs. 29.78%; P=0.38). The rate of life-bothering compensatory sweating was lower in the R4 sympathicotomy group compared with those of other two groups (0% vs. 25%, 47.8%; P=0.09). The rate of very satisfied to moderate grades of satisfaction were lower in the R3 sympathetic clipping group compared with those of other two groups (93.8%, 100% vs. 73.9%; P=0.07). The rate of recurrence/failure rates were lower in the R4 sympathicotomy group compared with those of other two groups (12.50% vs. 35.00%, 34.8%; P=0.25). Sympathetic surgery at the R3 level was the only significant risk factor for patient dissatisfaction (odd ratio =12.353, 95% confidence interval =1.376–110.914; P=0.025). Conclusions: Our data support that R4 sympathicotomy had lower grades of compensatory sweating, higher grades of satisfaction, and lower rates of recurrence/failure. We therefore consider R4 sympathicotomy as an optimal surgical treatment for palmar hyperhidrosis.